Root Guided Immediate Implant Placement at Mandibular Molar Site: A Case Report - Pradhan, Bismita; Joshi, SP; Sah, S (Journal of Nepalese Prosthodontic Society, 2019)
With the advancement in science and technology, Immediate implant placement has become a widely used and well accepted alternative to traditional treatment protocols. Post extraction implant placement in multicoated molar area is challenging. The primary stability in molar areas is achieved by engaging the interradicular bone but slipping of osteotomy drill to mesial or distal root socket during implant bed preparation is the main problem in post extraction immediate implant placement. Use of surgical guide, pre- extractive interradicular implant bed preparation and the combination of both these techniques has been used to overcome the problem related to immediate implant placement at molar sites. This paper presents an alternative approach in immediate Implant placement in multi rooted molar area that uses the anatomy and morphology of roots in guiding the osteotomy to provide an ideal3-dimensional implant positioning.